(untitled) (Journal of Hama University, 2019)
The research aims to identify the degree of prevalence of attachment patterns in a sample of students in the College of Education, and learn more about coping styles psychological common pressure among students. And defines the relationship between attachment patterns and methods of face psychological pressure. And measuring the level of significance differences in the answers to the research sample on attachment patterns Scale and coping styles of stress according to research variables (sex, school year). The researcher adopted the descriptive analytical method, the research sample consisted of 302 students from the Faculty of Education at the University of Damascus, and the researcher applying the attachment patterns of scale, and the scale of stress coping styles. The study concluded the following results: The most prevalent types of students are the first pattern: (safe attachment), who came in first place with an average (3.87), a high level, followed by a second attachment pattern was busied with an average (3.50). The more stress coping styles in common use among students is a method: (refrain cognitive), who came in first place with an average (3.28), a medium level, followed in second place blame and aggression by an average method (3.17). The existence of a correlation between stress coping styles and patterns of attachment parenting. There are no statistically significant differences between the average answers to the research sample differences on attachment parenting styles scale according to the variable sex.And no statistically significant between the average answers the research sample differences on attachment parenting styles scale according to the variable of the school year for the students in the fourth year. And the jirstyear between the average answers the research sample differences on a scale of psychological stress coping styles according to the sex variable in favor of male students. And the jirstyear significant between the average answers the research sample differences on a scale methods face psychological pressure variable according to the school year and for the fourth year students in positive ways. And for the first year students in the face of negative stress methods.